Oxyberberine, a novel gut microbiota-mediated metabolite of berberine, possesses superior anti-colitis effect: Impact on intestinal epithelial barrier, gut microbiota profile and TLR4-MyD88-NF-κB pathway. (February 2020) - Li, Cailan; Ai, Gaoxiang; Wang, Yongfu; Lu, Qiang; Luo, Chaodan; Tan, Lihua; Lin, Guosheng; Liu, Yuhong; Li, Yucui; Zeng, Huifang; Chen, Jiannan; Lin, Zhixiu; et al.
Graphical abstract: Abstract: Berberine (BBR), a naturally-occurring isoquinoline alkaloid isolated from several Chinese herbal medicines, has been widely used for the treatment of dysentery and colitis. However, its blood concentration was less than 1 %, and intestinal microflora-mediated metabolites of BBR were considered to be the important material basis for the bioactivities of BBR. Here, we investigated the anti-colitis activity and potential mechanism of oxyberberine (OBB), a novel gut microbiota metabolite of BBR, in DSS-induced colitis mice. Balb/C mice treated with 3 % DSS in drinking water to induce acute colitis were orally administrated with OBB once daily for 8 days. Clinical symptoms were analyzed, and biological samples were collected for microscopic, immune-inflammation, intestinal barrier function, and gut microbiota analysis. Results showed that OBB significantly attenuated DSS-induced clinical manifestations, colon shortening and histological injury in the mice with colitis, which achieved similar therapeutic effect to azathioprine (AZA) and was superior to BBR. Furthermore, OBB remarkably ameliorated colonic inflammatory response and intestinal epithelial barrier dysfunction. OBB appreciably inhibited TLR4-MyD88-NF-κB signaling pathway through down-regulating the protein expressions of TLR4 and MyD88, inhibiting the phosphorylation of IκBα, and the translocation of NF-κB p65 from cytoplasm to nucleus. Moreover, OBB markedly modulated the gut dysbiosis induced by DSS and restored the dysbacteria to normal level. Taken together, the result for the first time revealed that OBB effectively improved DSS-induced experimental colitis, at least partly through maintaining the colonic integrity, inhibiting inflammation response, and modulating gut microflora profile.